2016
DOI: 10.1095/biolreprod.116.140244
|View full text |Cite
|
Sign up to set email alerts
|

CDK2 Is Required for the DNA Damage Response During Porcine Early Embryonic Development

Abstract: Cyclin-dependent kinase (CDK) 2 inhibition plays a central role in DNA damage-induced cell cycle arrest and DNA repair. However, whether CDK2 also influences early porcine embryo development is unknown. In this study, we examined whether CDK2 is involved in the regulation of oocyte meiosis and early embryonic development of porcine embryos. We found that disrupting CDK2 activity with RNAi or an inhibitor did not affect meiotic resumption or meiosis II arrest. However, CDK2 inhibitor-treated embryos showed dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…However, we observed that EZH2 deficiency diminished genomic stability and induced apoptosis in cloned embryos. It was previously shown that EZH2 acts as an epigenetic determinant by inhibiting TNF-a-mediated apoptosis in colitis (47) and maintained T-cell genomic integrity by modulating DNA damage-induced apoptosis (34). Our findings highlight the important role of EZH2 for maintaining genomic stability and inhibiting apoptosis after SCNT reprogramming.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…However, we observed that EZH2 deficiency diminished genomic stability and induced apoptosis in cloned embryos. It was previously shown that EZH2 acts as an epigenetic determinant by inhibiting TNF-a-mediated apoptosis in colitis (47) and maintained T-cell genomic integrity by modulating DNA damage-induced apoptosis (34). Our findings highlight the important role of EZH2 for maintaining genomic stability and inhibiting apoptosis after SCNT reprogramming.…”
Section: Discussionsupporting
confidence: 63%
“…3J). g-H2AX is a marker for DNA double-stranded breaks (34), whereas ataxia-telangiectasia and Rad3related (ATR) and ataxia-telangiectasia mutated (ATM) are 2 genes that are activated in response to DNA damage (35). The g-H2AX level was higher in EZH2 knockdown 8-cell embryos compared with the control (Fig.…”
Section: Ezh2 Knockdown Reduces the Efficiency Of Bovine Scnt Reprogrmentioning
confidence: 95%
“…Most PA embryos that were treated with the RAD51 inhibitor or knockdown were arrested at approximately the four-cell stage on day 5, and these embryos showed increased DNA damage. In response to DNA damage, cell cycle checkpoints (G1, S, G2/M) are activated, stopping cell cycle progression to allow time for repair, thereby preventing the transmission of damaged or incomplete replicated chromosomes (Wang & Kim 2016). In somatic cells, insufficient DNA repair usually activates cell cycle checkpoints via the ATM and p53-p21 pathways (Espinosa et al 2003, Arias-Lopez et al 2006, Giono & Manfredi 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting was performed as described previously [30, 31], using the following antibody dilutions: anti-BCL-2, 1:500; anti-CDK1-pY15, 1:500; anti-cyclin B, 1:500; anti-β-actin, 1:2000.…”
Section: Methodsmentioning
confidence: 99%